2001
DOI: 10.1097/00007435-200107000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Syphilis and Fluorescent Treponemal Antibody Test Reactivity After the Age of 1 Year

Abstract: A reactive FTA-ABS may be seen at 12 months in children with and without evidence of congenital syphilis at birth. Not all children with congenital syphilis will manifest reactive FTA-ABS at 12 months, and FTA-ABS reactivity wanes with time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0
2

Year Published

2008
2008
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…A titer in the infant's serum that is higher than the mother's titer by 4-fold or greater at delivery is strongly suggestive of congenital infection (107). However, the absence of an infant's titer that is higher than the mother's titer by 4-fold or greater does not exclude the possibility of congenital infection as studies of serum pairs from infected mothers and infants show that fewer than 30% of infants have higher titers than their mothers (110). IgM antibodies can be detected in more than 80% of symptomatic infants, but data on the sensitivity of antibody assays in asymptomatic infants are limited (111,112).…”
Section: Prenatal Syphilis Screening and Congenital Syphilismentioning
confidence: 99%
See 1 more Smart Citation
“…A titer in the infant's serum that is higher than the mother's titer by 4-fold or greater at delivery is strongly suggestive of congenital infection (107). However, the absence of an infant's titer that is higher than the mother's titer by 4-fold or greater does not exclude the possibility of congenital infection as studies of serum pairs from infected mothers and infants show that fewer than 30% of infants have higher titers than their mothers (110). IgM antibodies can be detected in more than 80% of symptomatic infants, but data on the sensitivity of antibody assays in asymptomatic infants are limited (111,112).…”
Section: Prenatal Syphilis Screening and Congenital Syphilismentioning
confidence: 99%
“…Passively transferred antibodies can persist in an infant up to age 15 months, and, as such, a reactive TT after age 18 months is diagnostic of congenital syphilis; such infants require full evaluation and treatment for congenital syphilis if treatment was not provided or if treatment can be deemed to have been inadequate by a review of the treatment history (116). A study using the FTA-ABS test showed that only about half of the group of infants with clinical or laboratory evidence of congenital syphilis at birth had reactive FTA-ABS results at 12 months of age (110). A recent Canadian case series of infants with congenital syphilis reported that 69% of infants showed seroreversion in their treponemal tests by 18 months and that infants who did not show seroreversion in their TT were statistically more likely to have had delayed treatment and to have had higher maternal RPR titers at birth (117).…”
Section: Prenatal Syphilis Screening and Congenital Syphilismentioning
confidence: 99%
“…Treponemal tests include the serum fluorescent treponemal antibody absorption (FTA-ABS) test, the T. pallidum hemagglutination (TPHA) test, the enzyme immunoassay (EIA), and the Western blot (WB) assay (12, 13). In addition, chemiluminescent immunoassays (CLIA), such as the chemiluminescent microparticle assay (CMIA), and an even newer multiplex flow immunoassay (MFI), performed with recombinant antigens, are widely used in developed countries, where many laboratories have adopted the "reverse algorithm" for syphilis diagnosis (14,15).A Ն4-fold titer in the nontreponemal tests in the infant at delivery as opposed to that in the mother's serum is strongly suggestive of congenital infection, but the absence of a Ն4-fold titer does not exclude congenital infection (8)(9)(10)(11).Immunoglobulins M are considered key markers of fetal infection since they cannot cross the placental barrier. IgM antibodies can be found at birth in Ͼ80% of symptomatic infected infants, while data on the sensitivity in asymptomatic babies are limited (8).…”
mentioning
confidence: 99%
“…Due to the frequent absence of specific signs of infection at birth, serology has a pivotal role in CS diagnosis: all infants born to mothers with reactive syphilis test results should be tested in parallel with their own mothers (8)(9)(10)(11). Serological tests for syphilis are divided into nontreponemal and treponemal.…”
mentioning
confidence: 99%
See 1 more Smart Citation